The wife's tale : a novel - Lansens, Lori (Little, Brown and Co., 2010)
On the eve of their Silver Anniversary, Mary Gooch is waiting for her husband Jimmy to come home. As night turns to day, it becomes frighteningly clear to Mary that he is gone. Through the years, disappointment and worry have brought Mary's life to a standstill, and she has let her universe shrink to the well-worn path from the bedroom to the refrigerator. But her husband's disappearance startles her out of her inertia, and she begins a desperate search.